Diastereoselective amidoalkylation of (3S,7aR)-6-benzyl-7-hydroxy-3-phenyltetra-hydro-5H-imidazo[1,5-c][1, 3]thiazol-5-one : a short and highly efficient synthesis of (+)-biotin - Chavan, Subhash P.; Chittiboyina, A. G.; Ravindranathan, T.; Kamat, Subhash K.; Kalkote, Uttam R. (Journal of Organic Chemistry, 2005)
A short and highly efficient synthesis of W-biotin in 10 steps with 20% overall yield has been achieved from L-cysteine involving amidoalkylation of hydroxy imidazothiazolone 4 via an acyliminium ion intermediate to furnish C-7-substituted imidazothiazolones 5b as the key step.

Simple, concise, stereocontrolled synthesis of (8E,10Z)-pentadecadien-1-ol acetate - Chavan, Subhash P.; Kharul, Rajendra K.; Kamat, Subhash K.; Kalkote, Uttam R.; Kale, R. R. (Synthetic Communications, 2005)
A simple, concise, and stereocontrolled synthesis of (8E, 10Z)-pentadecadien-l -ol acetate involving a Cadiot-Chodkiewicz reaction as the key step is described.
Keywords: acetate; Acrobasis vaccini; Cadiot-Chodkiewicz reaction; diacetylene; Pheromone

Unusual stereochemical outcome of radical cyclization: synthesis of (+)-biotin - Chavan, Subhash P.; Chittiboyina, A. G.; Ramakrishna, G.; Tejwani, R. B.; Ravindranathan, T.; Kamat, Subhash K.; Rai, B.; Sivadasan, L.; Balakrishnan, K.; Ramalingam, S.; Deshpande, V. H. (Tetrahedron, 2005)
An enantioselective synthesis of (+)-biotin 1 starting from naturally available cysteine is described. The key steps are the unusual stereochemical outcome of radical cyclization of compound 10 to prepare 5,5-fused system 11, and the introduction of C4-sidechain at C-6 in 13 via a Grignard reaction. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: biotin; exocyclization; radical cyclization